Charlie Bumpers vs. the Teacher of the Year - Harley, Bill, 1954- (Peachtree Publishers, 2013)
Charlie Bumpers is sure he does not stand a chance of getting along with his fourth grade teacher and despite his best efforts to be neat and well-behaved, he always seems to be in trouble until he discovers her secret.